2016
DOI: 10.1016/j.ntt.2016.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Multiple sevoflurane exposures in infant monkeys do not impact the mother-infant bond

Abstract: Exposure to general anesthesia during the postnatal period is associated with death of brain cells as well as long-term impairments in cognitive and emotional behavior in animal models. These models are critical for investigating mechanisms of pediatric anesthetic neurotoxicity as well as for testing potential strategies for preventing or mitigating this toxicity. Control conditions for anesthesia exposure involve separation of conscious infants from their mothers for variable periods of time, which could have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…Thus, on average, control infants experienced 30e40 min of maternal separation and were returned to the dam. Motherinfant interactions after these separations did not differ between groups, 23 indicating that the separations involved in anaesthesia exposures did not cause alterations in motherinfant bonding that might have impacted later cognitive or socio-emotional behaviour.…”
Section: Methodsmentioning
confidence: 90%
“…Thus, on average, control infants experienced 30e40 min of maternal separation and were returned to the dam. Motherinfant interactions after these separations did not differ between groups, 23 indicating that the separations involved in anaesthesia exposures did not cause alterations in motherinfant bonding that might have impacted later cognitive or socio-emotional behaviour.…”
Section: Methodsmentioning
confidence: 90%
“…Thus, on average, control infants experienced 30-40 min of maternal separation and were returned to the dam. Details of the mother-infant interactions after these separations have been published 24 and did not differ between groups, indicating that the separations involved in anaesthesia exposures did not cause alterations in mother-infant bonding that might have impacted later cognitive or socioemotional behavior. Editor's key points…”
Section: Methodsmentioning
confidence: 96%
“…Monkeys were evaluated on the human intruder test, an often-used measure of emotional reactivity in NHPs, when they were 6 months old, and the SEVO-treated monkeys exhibited significantly increased frequency of anxiety-related behaviors compared with the control group. In subsequent work, Raper et al presented evidence suggesting that the observed emotional disturbances in SEVO-treated monkeys were not likely due to differences in mother-infant bonding occurring in the drug and control groups (Raper, Bush, Murphy, Baxter & Alvarado, 2016). No neuropathological findings were reported in these studies.…”
Section: Animal Models Used To Assess the Functional Consequences Of mentioning
confidence: 99%
“…There is evidence that developmental ASA exposure induces alterations in emotionality, although concentrated study of this domain is relatively lacking. For example, several rodent and NHP studies have reported alterations in activity [e.g., Fredriksson et al, 2004; 2007 (mouse); Zheng et al, 2013 (rat)]; and anxiety-like behaviors [Man et al, 2015 (mouse); Raper et al, 2016; and Coleman et al, 2017 (monkey)] as a result of neonatal ASA exposure. During the early post-weaning period (P23) we recommend evaluating mice on their reactivity and habituation to handling (Gallitano-Mendel, Wozniak, Pehek, & Milbrandt, 2008).…”
Section: Extending Rodent Behavioral Models Through Analyses Within Fmentioning
confidence: 99%